KAJIAN KEBIJAKAN PPN ATAS BAHAN BAKAR MINYAK UNTUK KAPAL TUJUAN INTERNASIONAL (STUDY ON VALUE ADDED TAX POLICY ON INTERNASIONAL BUNKER FUEL) - Widia, I Nyoman (Badan kebijakan Fiskal, 2010)
This study focus on value added tax policy on international bunker fuel. Current regulation in Indonesia describes that government has imposed value added tax 10% on bunker fuel. Qualitative Approach was used in this study. As a result, imposing value added tax on bunker fuel against the international best practice. According to Value Added Tax Law, Government of Indonesia may give an incentive on bunker fuel.